ТЕХНИКА ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИДА ТАЛАБАЛАРНИНГ ТАДҚИҚОТЛИ КОМПЕТЕНЦИЯСИНИ РИВОЖЛАНТИРИШ ОМИЛЛАРИ - Ўктамова, Ш.Ҳ. (SCIENCE and SOCIETY, 2022)
The conducted theoretical analysis allows to distinguish the criteria for the development of research competence of students at technical higher education institutions. The article states that the pedagogical conditions for the organization of the educational process have been formed, according to which the development of research competence of graduates will serve to increase the effectiveness of the educational environment of the institute.
Keywords: research competence; technical higher education institutions; students; pedagogical staff; education